The efficacy data of two household cleaning and disinfecting agents on Lens culinaris Medik and Vicia faba seed germination - Abou Elezz, Ahmed (2021)
A germination test of Vicia faba and Lens culinaris seeds under the effect of bleach and vinegar was conducted for seven days, and the observations were recorded daily. The completely randomized design (CRD) was used to examine the germination with three replicates at the lab conditions. Six germination parameters were measured, including germination percentage (GP), germination index (GI), mean germination time (MGT), mean germination rate (MGR), vigour index (VI), plus the fresh weight (FW) and dry weight (DW) of Vicia faba and Lens culinaris seeds. As a legume crop seeds model, the efficacy of four treatment levels from 0.005% to 0.5% of bleach and vinegar on the germination was tested. A chemical analysis was performed using the ion chromatography (IC) to evaluate the effect of chloride and acetate anions uptake on the seedling germination in addition to other essential nutrients. A significant inhibition in seedling growth was observed with increasing the treatment concentration. The maximum inhibition was recorded for both seeds at 0.5%, followed by 0.1% levels, while a positive effect was represented with the lower concentrations. The chemical analysis of the up taking active ingredients was corroborated the germination outputs.